Staphylococcus aureus causing primary foot botryomycosis mimicking actinomycetoma: a case report from Sudan. (November 2022) - Siddig, Emmanuel Edwar; Nyuykonge, Bertrand; Bakheit, Osama EL Hadi; Hassan, Omnia Babekir; Ahmed, Eiman Siddig; Osman, Asma Adam; Bakhiet, Sahar Mubarak; van de Sande, Wendy WJ; Fahal, Ahmed Hassan
Highlights: Botryomycosis is a chronic granulomatous disease often caused by Staphylococcus aureus. Botryomycosis mimics actinomycetoma clinically and radiologically. Molecular identification can differentiate the two. Gram stain can be used to differentiate botryomycosis and actinomycetoma grains. Abstract: Objectives: Botryomycosis is a rare chronic granulomatous inflammatory disease of bacterial origin. Two forms of the disease exist; the cutaneous and the visceral form. The subcutaneous form mimics actinomycetoma clinically and histologically; however, the treatment is different. In this communication, we report on a Sudanese male patient who presented with foot botryomycosis. Design: Case report. Results: The patient was initially diagnosed with actinomycetoma by the presence of Streptomyces somaliensis like-grains in the histological slides. The patient was treated with a combination of co-trimoxazole and amikacin sulfate and shifted after 1 year to co-trimoxazole, amoxicillin, and clavulanic acid. Despite treatment, the infection progressed, and the bone was invaded. The infected limb was amputated. The histopathological report of the surgical biopsy showed gram-positive cocci inside the grain. The 16S sequence identified these cocci as Staphylococcus aureus. Conclusion: This is the first reported botryomycosis case from Sudan, and it highlights why molecular identification is vital in diagnosis.